Co-parenting and Father Involvement - Suzanna Smith (EDIS, 2009)
FAR0074, a 2-page transcript of the Family Album Radio Program broadcast by Suzanna Smith, describes research findings about the co-parenting relationships between custodial mothers and fathers living apart from their biological children. Published by the UF Department of Family Youth and Community Sciences, March 2009.